The Legal Dynamics of Aru Fisherman in Improving Catch Welfare and Competition with Vessels from Outside Maluku - Irma Mangar; Asri Elies Alamanda; Hanin Alya’ Labibah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
The identification of transnational crimes is crucial not only because of the increasing cases of illegal fishing in Indonesia, which involve legal issues from other countries and call for effective law enforcement. concentrate on the welfare of catches produced by local Aru Islands fishermen. The descriptive analysis method is the research methodology used. By using a normative legal approach, data collection strategies use literature studies and documentary studies while the type of research used is qualitative research with primary and secondary data sources. The findings of this study are throughout 2017 until now the government has made efforts as much as possible on the fate of marine and local fishermen in the people of the Aru Islands district, seeing that all policies regarding the regulation of regional maritime boundaries no longer include the authority of the regional government but the duties and responsibilities of the Provincial Government.